Here is the question:

let f : A $\displaystyle \rightarrow$ B and g : B $\displaystyle \rightarrow$ C be functions.

i) show that if g $\displaystyle \circ$ f is injective, then f is injective

ii) show that if g $\displaystyle \circ$ f is surjective, then g is surjective.

Here is what I have so far:

$\displaystyle g \circ f : A \rightarrow C. $ Now assume that $\displaystyle g \circ f $ is injective. then $\displaystyle g \circ f $ is one to one and $\displaystyle g(f(x_1)) = g(f(x_2)) \Rightarrow f(x_1) = f(x_2) $

So from here I know the goal is to show that $\displaystyle f(x_1)=f(x_2) \Rightarrow x_1=x_2 $. But how?? my guess is that inverse functions are involved?? maybe not.

As far as part b goes, I'm thinking that it is a similar process, almost reversed. but I'm still somewhat confused on this part. thank you for the help!